Interfragmentary screws in Danis and Weber type B ankle fractures: is it necessary to maintain the stability of the joint? - Muñoz-Granja, Steve Jhosue; Guano Zambrano, Katherine Cristina; Proaño-Durán, Juan Carlos; García-Gudiño, Vanessa Michelle; Villarreal Enríquez, Josselyn Nicole (Sapienza: International Journal of Interdisciplinary Studies, 2023)
OBJECTIVE: This study aimed to investigate whether the presence or absence of an interfragmentary screw significantly impacts surgical time, bleeding, consolidation, complications, and overall recovery in patients with Weber type B ankle fractures. METHODS: A cross-sectional analytical study was conducted, involving 47 patients with Weber type B ankle fractures between January 2022 and January 2023 at San Francisco General Hospital in Quito. Patients with multi-fragment fractures were excluded. and two groups were established: patients with interfragmentary screws and those without. Variables such as surgical time, bleeding, complications, and consolidation time were assessed using JASP 0.16.0.0 software and statistical tests. RESULTS: Out of all patients, 53.19% were treated with interfragmentary screws, while 46.80% were not. No statistically significant differences were observed between the two groups. Complications occurred in 7 out of 25 patients with interfragmentary screws and in 4 out of 22 patients without them, with average follow-up periods of 82.81 and 76.8 days, respectively. Consolidation time was similar in both groups, with no statistical differences. CONCLUSION: Although interfragmentary screws are beneficial for achieving primary consolidation, this study suggests that they may not be universally necessary, especially when precise anatomical reduction is accomplished. Anatomical reduction remains pivotal in fracture management. While interfragmentary screws can provide compression, their use may increase costs, recovery time, and complications.